Impact of social media disinformation explored in 'The Social Dilemma' - Rizky Aditya Husandani; Prahastiwi Utari; Andre Noevi Rahmanto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
This study explored the significant impact of disinformation spread through social media, focusing on the documentary